Endophytic Occupation in Nodules of Rhynchosia Plants from Semiarid Regions of Argentina - Lucero, Cinthia T. (2024)
Beneficial microbes can improve soil health by promoting soil structure, nutrient cycling, and disease suppression. In addition, a wide array of rhizospheric microbes are responsible for producing metabolically active compounds including various types of plant growth regulators. So, microbial biodiversity studies could contribute to the improvement of agricultural practices in deprived areas, such as the Pampean semiarid region. The vast majority of studies conducted on endophytic microorganisms have focused on intensive crop legume species. In contrast, little attention has been paid to microorganisms of native legumes, whose ecology is not directly affected by human action. In this study, endophytic microorganisms isolated from root nodules of a selected native legume of the genus Rhynchosia were characterized. Viable isolates were studied with a focus on their plant growth-promoting rhizobacteria (PGPR) properties. Considering the edaphic characteristics of the Pampean semiarid region, the isolates obtained were evaluated for their ability to grow under three salt stress conditions (50, 100, and 200 mM NaCl) and four different pH values (6, 7, 8, and 9). Based on their PGPR activities, the selected strains were phylogenetically grouped using BOX-PCR. The results showed great variability among the isolates in terms of the characteristics studied. Native legumes manifested a wide endophytic variability and remarkable performance in PGPR activities. We conclude that they could be used as potential bioinoculants for legume cultivation, an excellent alternative to the use of chemical fertilizers that currently pollute the environment.